Mechanisms Fiscal Policy Transmission with Structure Vector Auto Regression Approach (S-Var) - Mursito, Hardian (Jurnal Multidisiplin Indonesia, 2024)
This study aims to analyze the transmission mechanism of fiscal policy in Indonesia using the Structure Vector Autoregression (S-VAR) approach, focusing on macroeconomic variables such as government spending, tax revenue, Gross Domestic Product (GDP), inflation, unemployment, and budget deficit over the period 2010 to 2020. The results of the analysis show that government spending has a significant positive impact on GDP growth, reflecting the effectiveness of expansionary fiscal policy in promoting economic growth and reducing unemployment in the short term. However, the impact on inflation shows complex dynamics, where inflation initially increases in response to government spending, but then stabilizes in the medium term. This finding indicates the need for careful management of fiscal and monetary policies to avoid undesirable inflationary impacts. In addition, Variance Decomposition analysis reveals that variations in GDP are influenced more by government spending than by other variables, emphasizing the important role of fiscal policy in the Indonesian economy. This study provides recommendations to increase spending in productive sectors while still monitoring inflation and budget deficit, which is expected to provide insights for policymakers in formulating economic growth strategies.